Komposisi botani dan produksi hijauan pakan serta kapasitas tampung padang penggembalaan alam musimkemarau di desa Kambata Wundut Kecamatan Lewa Kabupaten Sumba Timur - Mardianto Nggalumara; Herayanti Panca Nastiti; Dominggus B. Osa (Jurnal Peternakan Lahan Kering, 2019)
This study was carried out during 2 month on Natural Grassland area Kambata Wundut, Lewa sub-district, East Sumba Regency. The study almed at evaluating botany composition, forage production and cacry capacity of dry season pasture. Survey and and on the field measurement methods were used in the study. Forage production  was measured using Actual Weight Estimate method using 1m x 1m frame tool. Data were collected and tabulated to calculate botany precentage and composition, forage production and carry capacity of the pasture, Statistical analysis showed that Summed Dominance Ratio (SDR) 60,96%,(grass), 26,48% (weeds) and 12,56% ( legum); forage production 2,725 kg / Ha fresh or 2,082,9 kg / ha DM weight. in the pasture has a carry capacity1.02 AU / Ha / Year which for adult cattle weighing 300 Kg.